The Sheaths of Methanospirillum Are Made of a New Type of Amyloid Protein - Christensen, Line Friis Bakmann; Hansen, Lonnie Maria; Finster, Kai; Christiansen, Gunna; Nielsen, Per Halkjær; Otzen, Daniel Erik; Dueholm, Morten Simonsen (Frontiers in Microbiology, 2018)
The genera Methanospirillum and Methanosaeta contain species of anaerobic archaea that grow and divide within proteinaceous tubular sheaths that protect them from environmental stressors. The sheaths of Methanosaeta thermophila PT are composed of the 60.9 kDa major sheath protein MspA. In this study we show that sheaths purified from Methanospirillum hungatei JF-1 are regularly striated tubular structures with amyloid-like properties similar to those of Methanosaeta thermophila PT. Depolymerizing the sheaths from M. hungatei JF-1 allowed us to identify a 40.6 kDa protein (WP_011449234.1) that shares 23% sequence similarity to MspA from M. thermophila PT (ABK14853.1), indicating that they might be distant homologs. The genome of M. hungatei JF-1 encodes six homologs of the identified MspA protein. Several homologs also exist in the related strains Methanospirillum stamsii (7 homologs, 28-66% sequence identity), Methanospirillum lacunae (15 homologs, 29-60% sequence identity) and Methanolinea tarda (2 homologs, 31% sequence identity). The MspA protein discovered here could accordingly represent a more widely found sheath protein than the MspA from M. thermophila PT, which currently has no homologs in the NCBI Reference Sequence database (RefSeq).